Weather affects mobility but not mental well-being during lockdown - Ashley Burdett; Ben Etheridge; Lisa Spantig (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Mental well-being has declined during the Covid-19 pandemic in several developed countries, and particularly in the UK. Given the resurgence of the disease in western Europe during autumn 2020 and concurrently increasing restrictions, we investigate the possible effect on well-being of a winter lockdown. Using local variation during the spring lockdown in the UK, we found little effect of weather (temperature and rainfall) on well-being. This finding is despite a strong effect of weather on mobility in parks during the same period. Together, our results suggest a limited role for recreational mobility in maintaining well-being during this period. Our evidence suggests that winter weather will not exacerbate the well-being costs of lockdowns.
Keywords: 330; Mental well-being; Mental health; Weather; Mobility; Covid-19